PENGABDIAN KEPADA MASYARAKAT BERKELANJUTAN UJI KOMPETENSI SISWA SMK MUHAMMADIYAH PONTANG - Nugrahini Kusumawati; Ende Ende; Jaka Wijaya Kusuma; Hamidah Hamidah; Dini Martinda Lestari (Jubaedah : Jurnal Pengabdian dan Edukasi Sekolah (Indonesian Journal of Community Services and School Education), 2024)
This Community Service is carried out with the aim of knowing the achievement of knowledge and competence of SMK Muhammadiyah Pontang students in the field of Office Governance Automation and as a basis for preparing students to enter the world of work. The activity was held for 2 days followed by 29 class XII students majoring in Office Governance Automation. The method used by community service is as an external examiner for the Expertise Competency Test (UKK) where external examiners provide recommendations on the results of the Expertise Competency Test (UKK) that has been carried out by students. UKK is carried out with 4 stages, namely the preparation stage, the briefing stage, the implementation stage and the evaluation stage. The results of the student competency test showed that 28 students had Competent criteria and 1 student had Competent Enough criteria